2019
DOI: 10.1088/1755-1315/390/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Generation of plasma-activated water using a direct piezo-discharge: physicochemical aspects

Abstract: Recently, interest has grown in plasma-activated media (PAM) and, in particular, plasma-activated water (PAW) in connection with their extensive applications in medicine, pharmacology, agriculture and the food industry. In this paper, we studied the processes of production of reactive oxygen and nitrogen species (RONS) in distilled water under the influence of cold atmospheric plasma (CAP) generated by a source, based on the use of a piezotrans former. The first results obtained in the study of the UV absorban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The data showed that CAP water treatment provides a significant change of the liquid media properties. The PAW usefulness has already been revealed by long-term research in different scientific fields, including our contribution [25,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The data showed that CAP water treatment provides a significant change of the liquid media properties. The PAW usefulness has already been revealed by long-term research in different scientific fields, including our contribution [25,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrite ion (NO 2 − ) content in PAW increased according to the piezo-discharge exposure time. In 8 days after PAW producing, the nitrite ion partially transforms to the nitrate ion [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations